IMPLEMENTATION OF CONSUMER PROTECTION ON EXECUTION OF UNREGISTERED FIDUCIARY WARRANTYAT PT.FEDERAL INTERNATIONAL FINANCE (FIF) OF BENGKULU BRANCH - Septeddy Endra Wijaya; Slamet Muljono; Herawan Sauni (Universitas Bengkulu, 2021)
The execution of collateral in the financing institution as contained in the UUJF is clearly made by the creditor against the debtor whose is breach of contract, in which the execution of the creditor has a permanent legal forceand legitimate. However, for unregistered warranty in accordance with UUJFwould cause conflict. One of the conflicts that arises is the unprotected consumer rights. The purpose of this research is to understand and analyze the implementation of consumer protection on execution of fiduciary Warranty which is not registered at PT.Federal International Finance (FIF) of Bengkulu Branch. The method used was empirical juridical approach, by using qualitative analysis. Result of the research mentioned that implementation of consumer protection at execution of unregistered fiduciary Warranty at PT. Federal International Finance (FIF) of Bengkulu Branch was not in accordance with the provisions of applicable legislation where the execution of PT. Federal International Finance (FIF) of Bengkulu Branch was not accompanied by a fiduciary certificate and was not through previous mediation efforts so that the execution of non-registered fiduciary warrantyviolated the rights of the debtor as a consumer.